Chiral derivatization coupled with liquid chromatography/mass spectrometry for determining ketone metabolites of hydroxybutyrate enantiomers - Cheng, Qing-Yun; Xiong, Jun; Wang, Fang; Yuan, Bi-Feng; Feng, Yu-Qi (Chinese chemical letters, 2018)
Ketone bodies are small lipid-derived molecules and the metabolism of ketone bodies interfaces with various physiological processes. 3-Hydroxybutyric acid （3HB） is the most stable ketone body and can be employed to supply energy source. 2-Hydroxybutyric acid （2HB）, an isomer of 3HB, was demonstrated to be an early biomarker for both insulin resistance and impaired glucose regulation. Both 2HB and 3HB are chiral carboxylic acids and exist in two steric configurations （D/L-2HB and D/L-3HB）. It is difficult for these enantiomers to be differentiated by routine analytical methods In the current study, we developed a strategy by chiral derivatization coupled with liquid chromatography/mass spectrometry （LC-ESI-MS） analysis for simultaneous determination of D-2HB, L-2HB, D-3HB and L-3HB enantiomers. （5）-（＋）-l-（2- Pyrrolidinylmethyl）-pyrrolidine （PMP） was used for efficient labeling of HBs. Our results showed that the retention behavior of D/L-2HB and D/L-3HB enantiomers was greatly improved after labeling by PMP and the four derivatives can be distinctly separated on C18 reversed-phase column. Moreover, PMP chiral derivatization greatly enhanced the detection sensitivities of HBs up to 55.3 folds because of the introduction of easily ionizable tertiary amino group. Using this method, we simultaneously quantified D-2HB, L-2HB, D-3HB, and L-3HB enantiomers in human renal cell carcinoma （RCC） tissues and the tumor adjacent normal tissues. The result demonstrated that both D-3HB and L-3HB can be detected in human renal tissues, however, only L-2HB was detected in human renal tissues. In addition, the quantification results showed that the contents of D-3HB were approximate 10 folds higher than L-3HB. Taken together, the developed method offered an efficient approach for the sensitive analysis of D/L-2HB and D/L-3HB enantiomers, which may facilitate the in-depth study of the functions of HBs.